Pengaruh Konsumsi Air Kelapa Hijau dalam Penurunan Intensitas Dismenore di Sumatera Selatan - Sumantri; Kurnia Sari (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2023)
ABSTRACTBackground: Dysmenorrhea in adolescents usually occurs due to very high prostaglandin hormones on the first day of menstruation. Dysmenorrhea affects productivity such as disruption of learning activities causing a lack of focus in lessons and can even increase absenteeism from school. One effort that can be done to relieve dysmenorrhea is non-pharmacological therapy of green coconut water. Green coconut water contains vitamins and minerals that can stimulate the body to stabilize the prostaglandin hormone so that dysmenorrhea pain decreases.Research Objectives: This study aims to determine the effect of consuming green coconut water (Cocos Nucifera Linn Var. Viridis) on reducing the intensity of dysmenorrhea in young women in Sungai Pinang 1 Village, Ogan Ilir District, South Sumatra.Research Methods: The type of research used is a quantitative research with a quasi-experimental design with a one group pretest and posttest serial design. Total sampling data collection technique obtained. The data analysis used non-parametric statistics because the data were not normally distributed, the Wilcoxon test was used with a significant level of 0.05. Results: there was a decrease in the intensity of pain response before treatment pain score 128 with a mean score of 4.74 (moderate pain) after treatment I, II and III there was a decrease in pain score 72 with a mean score of 2.77 (mild pain). Green coconut water has a significant effect on reducing the intensity of dysmenorrhea with a significant level of p 0.000 Z score -4.633 (Z score table = 107).Conclusion: There is a significant effect on reducing the intensity of dysmenorrhea after consuming green coconut water in young women in Sungai Pinang 1 Village, Ogan Ilir District.Keywords: Green coconut water, dysmenorrhea, pain intensity